(untitled) (Research, Society and Development, 2020)
Objective: To analyze the historical series of the prevalence of hospitalization for stroke in children and adolescents in the last 18 years. Method: this is a historical series, with data referring to the years 1998 to 2016, collected through the database, DATASUS. Through the link, the TABNET page will be accessed. The raw data were transcribed into an Excel program table (Version 2010) and will undergo simple statistical analysis (calculation of prevalence and simple descriptive analysis). Results: In Brazil, the highest prevalence rate was 1.18 / 100,000 children, occurred in 2014. There is a growing trend both in the number of hospitalizations for stroke in children, as well as an increasing prevalence of this in the pediatric population. The age group from 15 to 19 years old is the most affected, while the period from 4 to 9 years old is the least frequent in hospitalizations. Conclusion: The increase in the prevalence of hospitalization rates due to stroke in children and adolescents stands out, which represents demands for health services, both in hospitals and in primary care.